ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI PADI (Oryza Sativa L.) DI DESA SB. USRAT KECAMATAN JAWAI KABUPATEN SAMBAS - Istiqomah, Ayu; Yurisinthae, Erlinda; Kurniati, Dewi (Jurnal Sains Mahasiswa Pertanian, 2018)
ABSTRACTSB.Usrat is one of the villages in Jawai sub district where some people work as farmers who participate in producing rice to meet the needs of rice in the village. Government-backed farmers are working to increase rice production in order to meet the increasing demand for rice caused by the increasing consumption of the community. In realizing sustainable agriculture and in an effort to increase production farmers need to utilize production factors effectively and efficiently. This study uses quantitative data types with the method used in this study is multiple regression analysis with the help of SPSS (Statistical Product and Service Solutions) 18.0 for windows applications. The results showed that multiple regression analysis was Y = -119.282 + (-2.388)X1 + 1975.153X2 + 35.670X3 + 2.626X4 + 45.891X5 + 16.416X6, the simultaneous test obtained 0.000 < 0.1. This shows that the overall variables of age, land area, education, farming experience, interaction with extension workers, and involvement in farmer groups have significant effect on rice production at a significant level of 10%. Based on the result of t test indicate that variable of land and education have significant effect to rice farming production, while age, farming experience, interaction with extension agent, and involvement in farmer group have no significant effect on rice production.Keywords: District Jawai, Farming Rice, Production